2013
DOI: 10.1002/jrs.4266
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of combinatory anticancer drug release from gold nanoparticles inside a single leukemia cell

Abstract: Combinatory anticancer drug release from gold nanoparticles (AuNPs) in K562 human myeloid leukemia cells was performed using Raman spectroscopy. We fabricated the anticancer drug of imatinib as a BCR‐ABL tyrosine kinase inhibitor on AuNP surfaces along with a transferrin (Tf)‐targeting moiety to treat the leukemia cells. DNA topoisomerase I inhibitor topotecan was also assembled to monitor its fluorescence onto AuNPs. The linker group of 4‐carboxylic benzoic acid was used to conjugate to targeting the Tf prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Topo is a DNA topoisomerase I inhibitor that acts as a fluorescent-reporter molecule, while CBT targets transferrin protein. Raman spectroscopy and dark-field microscopy studies confirmed that the nanoconjugate entered into the K562 cells via the receptor-mediated endocytosis and released the drugs (IM and Topo) after glutathione (2 mM) treatment [138].…”
Section: Gene Therapymentioning
confidence: 73%
See 1 more Smart Citation
“…Topo is a DNA topoisomerase I inhibitor that acts as a fluorescent-reporter molecule, while CBT targets transferrin protein. Raman spectroscopy and dark-field microscopy studies confirmed that the nanoconjugate entered into the K562 cells via the receptor-mediated endocytosis and released the drugs (IM and Topo) after glutathione (2 mM) treatment [138].…”
Section: Gene Therapymentioning
confidence: 73%
“…TKI, IM is used as a first-line treatment for CML with BCR-ABL1 gene fusions [137]. Ganbold et al (2013) [138] conjugated IM, topotecan (Topo), and 4-carboxylic benzoic acid (CBT) on the surface of AuNPs. Topo is a DNA topoisomerase I inhibitor that acts as a fluorescent-reporter molecule, while CBT targets transferrin protein.…”
Section: Gene Therapymentioning
confidence: 99%
“…Their results indicated that the drug molecules were not detached in the cell culture media but released after treatment with glutathione. [89] Jehlicka and Oren demonstrated the use of a handheld Raman spectrometer for fast screening of microbial pigments in cultures of halophilic microorganisms and in microbial communities in hypersaline environments in nature. To their knowledge this work represents the first attempt to detect and identify pigments in natural microbial communities consisting of different types of halophilic microorganisms by direct Raman spectrometric measurements using light compact handheld devices.…”
Section: Biomoleculesmentioning
confidence: 99%
“…Ganbold and coworkers carried out combinatory anticancer drug release from gold NPs (AuNPs) in K562 human myeloid leukemia cells using Raman spectroscopy. Their results indicated that the drug molecules were not detached in the cell culture media but released after treatment with glutathione . Jehlicka and Oren demonstrated the use of a handheld Raman spectrometer for fast screening of microbial pigments in cultures of halophilic microorganisms and in microbial communities in hypersaline environments in nature.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Dark field imaging which works through obtaining the scattering light of samples is an effective technique to observe live and unstained biotissues. 10,11 Furthermore, it is also suitable to observe nano-sized samples with the size beyond the light diffraction limit. 12,13 Combining these imaging techniques with Raman microspectroscopy, the research fields of Raman could be significantly expanded.…”
mentioning
confidence: 99%